2011
DOI: 10.1053/j.gastro.2011.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Differential, Type I Interferon-Mediated Autophagic Trafficking of Hepatitis C Virus Proteins in Mouse Liver

Abstract: BACKGROUND & AIMS The hepatitis C virus (HCV) serine protease NS3/4A can cleave mitochondria-associated, anti-viral signaling protein (MAVS) and block retinoic acid-inducible gene I–mediated interferon (IFN) responses. Although this mechanism is thought to have an important role in HCV-mediated innate immunosuppression, its significance in viral persistence is not clear. METHODS We generated transgenic mice that express the HCV NS3/4A proteins specifically in the liver and challenged the animals with a recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…66 In addition, through nucleotide-binding oligomerization domain 1, Ifnb1 also partially protects the infected host by decreasing H. pylori gastric colonization. 67 We observed significant upregulation of hepatic Ifnb1 in HT female Hp mice relative to WT female Hp mice suggesting that the HCV transgene contributed to a type I interferon response during H. pylori infection.…”
Section: Hcv Transgene Increases Serum Tnf-α During H Pylori Infectimentioning
confidence: 99%
See 1 more Smart Citation
“…66 In addition, through nucleotide-binding oligomerization domain 1, Ifnb1 also partially protects the infected host by decreasing H. pylori gastric colonization. 67 We observed significant upregulation of hepatic Ifnb1 in HT female Hp mice relative to WT female Hp mice suggesting that the HCV transgene contributed to a type I interferon response during H. pylori infection.…”
Section: Hcv Transgene Increases Serum Tnf-α During H Pylori Infectimentioning
confidence: 99%
“…Five micrograms of RNA were converted to cDNA using High Capacity cDNA Reverse Transcription Kit (Applied Biosystems). Gastric and hepatic gene expression of Tumor necrosis factor (Tnf ) (Assay ID: Mm99999068_m1), Interferon gamma (Ifng) (Assay ID: Mm01168134_m1), Interferon β 1, fibroblast (Ifnb1) 66 (Assay ID: Mm00439546_s1), Interleukin 10 (Il10) (Assay ID: Mm01288386_m1) were measured using commercial TaqMan® primer-probe sets (Applied Biosystems-Life Technologies). The volume of each reaction consisted of 5 μl of sample cDNA, 4 μl of UltraPure™ Distilled Water (GibcoLife Technologies, 10977), 1 μl of primer-probe, and 10 μl of TaqMan® Fast Universal PCR Master Mix (2×) (Applied Biosystems, 4352042).…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…Consistent with the inability of MCF-7 cells to induce activation of caspase-3,28 pretreatment with the pan-caspase inhibitor Z-VAD did not affect the cell viability seen after the treatments (Figure 4D). Although it is known that autophagy is required for the production of IFNα by plasmacytoid dendritic cells during viral infection,40 and it has been recently shown that type I IFN induces autophagic trafficking of viral proteins of hepatitis C virus,41 the role of IFNα in the autophagy process is still unclear and knowledge is restricted to its antiviral function. Our results show, for the first time, evidence that IFNα is involved in the autophagy process in combination with an antitumor agent.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, distinct autophagic pathways were found to result in IFN-β or IFN-α signaling, in a model of viral infection [119]. IFN-β, which is first produced by hepatocytes upon viral detection (VSV or a synthetic HCV genome), was found to signal in order to orientate viral proteins towards an autophagic degradation, within autolysosomes.…”
Section: Autophagy In Type I Ifn Signalingmentioning
confidence: 99%